1989
DOI: 10.1128/mcb.9.3.1173
|View full text |Cite
|
Sign up to set email alerts
|

Nonrandom distribution of long mono- and dinucleotide repeats in Drosophila chromosomes: correlations with dosage compensation, heterochromatin, and recombination.

Abstract: Long stretches of (dC-dA)n.(dT-dG)n, abbreviated CA/TG, have a distinctive distribution on Drosophila chromosomes (M.L. Pardue, K. Lowenhaupt, A. Rich, and A. Nordheim, EMBO J. 6:1781-1789, 1987). The distribution of CA/TG suggests a correlation with the overall transcriptional activity of chromosomal regions and with the ability to undergo meiotic recombination. These correlations are conserved among Drosophila species and may indicate one or more chromosomal functions. To test the generality of these finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 22 publications
6
47
0
Order By: Relevance
“…Sequences containing the GAGA motif appear to have an important role in attracting the DCC to the roX2 high-affinity site (Park et al 2003), and have also been found in additional high-affinity sites (Dahlsveen et al 2006). Furthermore, CA and GA dinucleotide repeats are enriched on the X chromosomes of Drosophila species exhibiting dosage compensation (Huijser et al 1987;Pardue et al 1987;Lowenhaupt et al 1989). Whether sequence motifs, in complex combinations, are sufficient to explain all DCC targeting is currently unclear.…”
Section: Dna Sequence Elements May Attract the DCC To Target Genesmentioning
confidence: 99%
“…Sequences containing the GAGA motif appear to have an important role in attracting the DCC to the roX2 high-affinity site (Park et al 2003), and have also been found in additional high-affinity sites (Dahlsveen et al 2006). Furthermore, CA and GA dinucleotide repeats are enriched on the X chromosomes of Drosophila species exhibiting dosage compensation (Huijser et al 1987;Pardue et al 1987;Lowenhaupt et al 1989). Whether sequence motifs, in complex combinations, are sufficient to explain all DCC targeting is currently unclear.…”
Section: Dna Sequence Elements May Attract the DCC To Target Genesmentioning
confidence: 99%
“…However, runs of (CG) m are observed more rarely than expected, given the frequency of CG dinucleotides (Tautz et al 1986;Jurka and Pethiyagoda 1995). Additionally, (CG) m repeats are rare, even in Drosophila, which does not have C methylation or under-representation of CG dinucleotides (Lowenhaupt et al 1989;Stallings 1992). Our results indicate that (CA) n -repeat-containing regions appear enriched for contiguous runs of (CG) m , in comparison with other genomic regions.…”
Section: Discussionmentioning
confidence: 61%
“…The conformational change need only occur at such a time when the recombinase system is present, to facilitate the formation of a chromosome aberration. There is much evidence to show that potential Z-DNA is a very minor fraction of genomes (Braaten et al, 1988), is non-randomly distributed (Pardue et al, 1987;Braaten et al, 1988;Hellman et al, 1988;Lowenhaupt et al, 1989) and further that proteins can be detected which bind to such regions (Fishel et al, 1988;Leith et al, 1988 The data presented here also show that the region adjacent to pu -py tracts in the chromosome frequently possesses a site with hypersensitivity to DNase I digestion. Clearly it is not possible to say whether these sites are related to the existence of the pu-py tract or not, since, in both cases studied, they occur -2 kb away from the pu-py stretch.…”
mentioning
confidence: 57%